Habakkuk 2.4b in its Context: How Far Off Was Paul? - Hunn, Debbie (Journal for the study of the Old Testament, 2009)
This essay examines Hab. 2.4b in its context, asking five questions related to Paul’s exegesis, namely: What is ‭הנומא‬? Whose ‭הנומא‬ is at issue? When will the righteous live? Who are the righteous? And are they righteous by faith, or do they live by faith? Although scholars have changed their reading of Paul over time, they have left Habakkuk almost untouched. And yet, an examination of his prophecy finds Habakkuk, before Paul, to include both Jew and Gentile among the righteous and to assert that life comes to the righteous by their faith.